2020
DOI: 10.3390/jcm9124093
|View full text |Cite
|
Sign up to set email alerts
|

Affecting Factors and Correction Ratio in Genu Valgum or Varum Treated with Percutaneous Epiphysiodesis Using Transphyseal Screws

Abstract: This study evaluated the correction rates of idiopathic genu valgum or varum after percutaneous epiphysiodesis using transphyseal screws (PETS) and analyzed the affecting factors. A total of 35 children without underlying diseases were enrolled containing 64 physes (44 distal femoral (DT), 20 proximal tibial (PT)). Anatomic tibiofemoral angle (aTFA) and the mechanical axis deviation (MAD) were taken from teleroentgenograms before PETS surgery and screw removal. The correction rates of the valgus and varus defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…This is the originality of this study, which is different from previous studies on hemi-PETS. [6][7][8]11,12,17 Similar to our results of growth inhibition at the distal femur, Park et al 12 reported the overcorrection of the distal femur after hemi-PETS and screw removal, while the proximal tibia was stable. Different from their study, 12 we included surgery-related factors and concluded that an excessive peripheral position of a screw might be associated with excessive correction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is the originality of this study, which is different from previous studies on hemi-PETS. [6][7][8]11,12,17 Similar to our results of growth inhibition at the distal femur, Park et al 12 reported the overcorrection of the distal femur after hemi-PETS and screw removal, while the proximal tibia was stable. Different from their study, 12 we included surgery-related factors and concluded that an excessive peripheral position of a screw might be associated with excessive correction.…”
Section: Discussionsupporting
confidence: 85%
“…However, studies dealing with factors affecting postoperative courses after the removal of transphyseal screws are still rare and limited. 7,11,12 With this background, we conducted a study on hemi-PETS performed in adolescent patients with idiopathic genu valgum at our institution. The aim of our study was to investigate factors determining the final outcomes of hemi-PETS, especially focusing on postoperative courses after screw removal.…”
mentioning
confidence: 99%
“…It has recently been advocated by many surgeons, because it is a minimally invasive procedure compared with other methods that need a wider exposure. 8,10,15,17 However, physeal damage is one of concerns when performing PETS because it directly involves the physes. In our study, the mean rebound angle in the SG was 1.1 ± 3.1 degrees, and it was significantly lesser than that in the PG.…”
Section: Discussionmentioning
confidence: 99%
“…The principle finding of this study was that the use of tension-band plates and faster correction speed were associated with the rebound phenomenon after temporary hemiepiphysiodesis for idiopathic genu valgum in adolescent patients. Different from previous studies on temporary hemiepiphysiodesis for genu valgum, 3,4,[6][7][8][9][10]15 we analyzed various parameters including the type of implant based on the regression analyses to suggest significant factors of the rebound phenomenon. By referencing our results of the linear regression model (model 2 in Table 4), the use of tension-band plates (compared with transphyseal screws) averagely resulted in an increase of 1.7 degrees rebound angle, and an increase of 1 degrees/month correction speed averagely resulted in an increase of 1.7 degrees rebound angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation